2017
DOI: 10.1002/ange.201701225
|View full text |Cite
|
Sign up to set email alerts
|

From Two‐ to Three‐Dimensional Structures of a Supertetrahedral Boran Using Density Functional Calculations

Abstract: With help of the DFT calculations and imposing of periodic boundary conditions the geometrical and electronic structures were investigated of two-and three-dimensional boron systems designed on the basis of graphane and diamond lattices in which carbons were replaced with boron tetrahedrons.The consequent studies of two-and three-layer systems resulted in the construction of at hree-dimensional supertetrahedral borane crystal structure.T he two-dimensional supertetrahedral borane structures with less than seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Neither of the subsequently proposed various modifications of the diamond-like structures based on bridging carbon atoms with acetylene and bisacetylene linkers was found to excel diamond in density and hardness. 1,2 We have previously shown that the idea to use the diamond lattice as the template for the construction of stable crystal forms can be successfully exploited in the computational design of novel allotropic modifications of other than carbon main-group elements, superterahedral boron, 6 and supertetrahedral aluminum. 7 In the present paper, this approach is extended to the study of geometric and electronic structures of solids constructed on the basis of a diamond lattice in which pairs of the carbon atoms are replaced by Al 4 −X fragments, where atoms X (X = B, C, Al, Si) serve as the linkers between tetrahedral Al 4 units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Neither of the subsequently proposed various modifications of the diamond-like structures based on bridging carbon atoms with acetylene and bisacetylene linkers was found to excel diamond in density and hardness. 1,2 We have previously shown that the idea to use the diamond lattice as the template for the construction of stable crystal forms can be successfully exploited in the computational design of novel allotropic modifications of other than carbon main-group elements, superterahedral boron, 6 and supertetrahedral aluminum. 7 In the present paper, this approach is extended to the study of geometric and electronic structures of solids constructed on the basis of a diamond lattice in which pairs of the carbon atoms are replaced by Al 4 −X fragments, where atoms X (X = B, C, Al, Si) serve as the linkers between tetrahedral Al 4 units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The computational design of novel two-and three-dimensional materials with the nonstandard structures and potentially useful properties is rapidly growing into an important area of the materials science. We have previously theoretically predicted and investigated electronic and spatial structures of the new allotropic forms of supertetrahedral boron, 1,2 built on the basis of a diamond lattice in which carbon atoms were replaced by boron tetrahedrons. The logic of this replacement is based on the kinetic stability of the tetrahedral boron structure B 4 H 4, which, due to electron deficiency of a boron atom, does not conform to the global minimum at the corresponding potential energy surface (PES), but belongs to its local minimum and preserves stability under substitution of the hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%